Use of level specific CE-Chirp auditory brainstem response in infants with and without hearing impairment - Chahed, Norashikin; Dzulkarnain, Ahmad Aidil Arafat (2021)
Background: Universal Newborn Hearing Screening (UNHS) is part of the early hearing detection and intervention (EHDI) initiative that aims for early diagnosis, intervention, and follow-up, of hearing-impaired babies. One of the tools used for UNHS is the Auditory Brainstem Response (ABR). ABR can be elicited by many stimuli including LS CE Chirp, and previous studies reported that this most recent innovated stimulus has a lot of advantages; for instance, it provides most neural synchrony thus, produces larger amplitudes of waves I, III and V. To date, the knowledge on test-time efficiency of the ABR to LS CE-Chirp is limited and only reported from the adult population. This study aims to investigate the test-efficiency of the ABR elicited from LS CE Chirp stimulus in infants with or without hearing impairment. Method: A total of 70 infants ( 35 normal hearing, 35 hearing- impaired) age between 1 and 3 months old will participate in this study. The selected infants must have normal outer and middle ear function. ABR will be acquired using two stimuli (LS CE-Chirp and click) at 70, 30 dBnHL and continue until the auditory thresholds of the patients. The ABR will be acquired using three stimulus repetition rates ( 88.1, 66.1, and 33.3 cps), and the signal averaging will be stopped based on the following; (i) F test at multiple points equal to 3.1(ii) visual detection (iii) fixed signal average at 2500 sweeps. The ABR test time, amplitude, absolute latency, interpeak latencies ( IPL), and threshold estimation level will be recorded and statistically evaluated. Results: Two-Way Repeated measure ANOVA will be used to analyze ABR results (test time, amplitude, absolute latencies, interpeak latencies ( IPL), and auditory thresholds) elicited from LS CE-Chirp and click stimuli. The results will be compared between ABR to LS CE-Chirp and click stimulus within and between groups (normal hearing and hearing-impaired population). It is hypothesized that the ABR to LS CE Chirp will has shorter test time, larger amplitudes of waves I, III and V, longer absolute latencies of waves I, III and V, longer IPL of waves I-III, III-V and I- V than ABR to click stimulus among all combinations. This study also hypothesized that the ABR threshold levels from LS CE- Chirp is lowered than ABR to click stimulus. Conclusion: This study’s outcome can be used as a guideline or protocol for ABR test in pediatric, to serve a better health service to our next generation by maintaining the efficiency of aural rehabilitation in the way of early diagnosis and intervention.